Integrasi Ilmu Islam dan Sains: Landasan Epistemologis, Model, Implementasi, dan Tantangan - Ussy Susilawati; Syifaudin (PT. Hasba Edukasi Mandiri, 2026)
This research discusses the integration of Islamic knowledge and science as a paradigm that combines Islamic sciences with modern science within a unified epistemological framework. The background is the dichotomy between religious knowledge and general knowledge, which remains a problem in Islamic education. The objectives are to analyze the epistemological foundations, identify integration models, describe implementation, analyze challenges, and examine impacts on students. The method used is library research with a qualitative-descriptive approach. The findings show that knowledge integration has strong foundations in the holistic concept of Islamic knowledge and the principle of tauhid (monotheism). Various integration models have been developed, such as Al-Faruqi's Islamization of knowledge, Al-Attas's Islamization of present-day knowledge, and the integration-interconnection model. Its implementation faces epistemological, human resource, institutional, and socio-cultural challenges. Nevertheless, integration-based learning has positive impacts on conceptual understanding, learning motivation, and character formation of students. This research concludes that knowledge integration is an urgent necessity for the advancement of Islamic education and civilization.